2023
DOI: 10.1021/acs.jctc.3c00518
|View full text |Cite
|
Sign up to set email alerts
|

Low-Data Deep Quantum Chemical Learning for Accurate MP2 and Coupled-Cluster Correlations

Abstract: Accurate ab initio prediction of electronic energies is very expensive for macromolecules by explicitly solving post-Hartree–Fock equations. We here exploit the physically justified local correlation feature in a compact basis of small molecules and construct an expressive low-data deep neural network (dNN) model to obtain machine-learned electron correlation energies on par with MP2 and CCSD levels of theory for more complex molecules and different datasets that are not represented in the training set. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 66 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Bearing this in mind, in our electronic T-dNN model, we express the correlated descriptors 143 taking only a few OSVs, and we have found that the electron correlation characters are well reserved for making transferable prediction. Based on numerical experimentation, we define the feature amplitudes that respect the unique physical nature of the electron correlations according to the 2p-2h excitation patterns: vertical (vt, e…”
Section: Cheap Neural Network Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Bearing this in mind, in our electronic T-dNN model, we express the correlated descriptors 143 taking only a few OSVs, and we have found that the electron correlation characters are well reserved for making transferable prediction. Based on numerical experimentation, we define the feature amplitudes that respect the unique physical nature of the electron correlations according to the 2p-2h excitation patterns: vertical (vt, e…”
Section: Cheap Neural Network Learningmentioning
confidence: 99%
“…The basic idea is that, when the orbital‐based ab‐initio descriptors are expressed in sufficiently reduced low‐rank basis via single‐ (Section 2.2) or many‐particle (Section 2.3) rotations, the expense of computing these descriptors can be significantly lowered and the model transferability can be enhanced by learning simple molecules. Hence, we have developed a transferable deep neural network (T‐dNN) model 143 using OSV‐based descriptors for predicting chemically accurate MP2 and CCSD correlation energies from a small training set containing small molecules. The low‐rank OSV algorithm of these descriptors virtually compresses a global correlating environment for all electrons in the molecule into many local correlating environments, each for one electron, which simultaneously encodes the long‐range correlation and retains the transferable feature.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations